2019
DOI: 10.1007/978-3-030-18400-1_31
|View full text |Cite
|
Sign up to set email alerts
|

How South African University Information Systems Students Are Using Social Media

Abstract: Social media is a term used to combine social networking, media sharing and microblogging systems. Social media assists students to improve their academic studies, allows collaboration and sharing of information with each other, and affords students to know what is happening in the world, acquire pictures and videos in support of such information. Information Systems (IS) students are the next generation of technology experts and their exposure to using social media as an alternative source of information and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Facilitating conditions were expressed in the context of this research as students' views of whether they have access to the tools and assistance they need to utilize YouTube for Islamic information acquisition. Several social media researchers have found that the facilitating conditions are a reliable predictor of intention to utilize social media apps [47] [50]. Therefore, this research hypothesizes that when the ease of facilitating conditions improves, the student's use of YouTube videos for Islamic knowledge will develop.…”
Section: B Hypotheses Developmentmentioning
confidence: 94%
“…Facilitating conditions were expressed in the context of this research as students' views of whether they have access to the tools and assistance they need to utilize YouTube for Islamic information acquisition. Several social media researchers have found that the facilitating conditions are a reliable predictor of intention to utilize social media apps [47] [50]. Therefore, this research hypothesizes that when the ease of facilitating conditions improves, the student's use of YouTube videos for Islamic knowledge will develop.…”
Section: B Hypotheses Developmentmentioning
confidence: 94%